THE SOCIAL COST OF SUSTAINABILITY: SOCIO-ENVIRONMENTAL CONFLICTS IN MINAÇU AMID THE SHIFT FROM ASBESTOS TO RARE EARTH MINING (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
This study analyzes the social cost of sustainability through the case of Minaçu, Brazil, a municipality historically dependent on asbestos mining and now focused on rare earth extraction. The research seeks to understand the challenges of the ecological transition and its implications for the right to work, local development, and environmental protection. A deductive–inductive approach is adopted, combining bibliographic and documentary methods to examine the economic, social, and legal consequences of the asbestos mining shutdown and the productive reconfiguration of the region. The findings show that the absence of integrated public policies to convert traditional employment into “green jobs” has increased social vulnerability and hindered the implementation of a just transition. Moreover, persistent conflicts between government branches and private actors highlight the tension between the social right to work and the fundamental right to an ecologically balanced environment in the context of rare earth mining.Keywords: sustainability. Ecological transition. Asbestos. Rare earths. Minaçu. Green jobs.